Optimalisasi Peer Counseling dalam Program Bestie Talks untuk Meningkatkan Kesiapan Menikah - Nida Muthi Annisa; Albin Prayoga; Devanan Mangaratua Sagala (Ma'soem University, 2026)
Marriage readiness is a crucial aspect in building a harmonious and sustainable family life. Lack of psychological and emotional readiness, as well as communication skills, often triggers conflict in households. Therefore, preventive measures are needed through educational activities and community empowerment. This community service program aims to improve understanding and marriage readiness through a peer counseling approach for young adults. The peer counseling approach was chosen because peer interactions tend to create a more open and supportive communication atmosphere. This activity was attended by 12 young adult women, with one counseling session. The results showed an increase in participants' understanding of marriage readiness. These findings suggest that peer counseling programs can be an effective educational strategy in increasing marriage readiness in the community, particularly among young adults.